EMERGENCY REMOTE TEACHING: EDUCATIONAL STRATEGIES ADOPTED IN PRACTICAL ACTIVITIES IN GASTRONOMY DURING THE COVID-19 PANDEMIC (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2023)
This research to identify the educational strategies adopted by the higher education course in gastronomy technology at the Federal Institute of Santa Catarina to enable practical non-presential classes during the pandemic. For this, an online focus group was carried out with teachers of the course. Teachers with backgrounds in different areas of knowledge participated, with extensive national and international experience in gastronomy, high level of education, and with professional performance at different educational levels. With the results, three pedagogical models were identified and described to enable remote practical classes. These models use a synchronous class with cooking preparations in real time or previously recorded. As well as, in asynchronous classes, students exercise the skills and techniques demonstrated in the synchronous class. The models use the same virtual learning environments, and different assessment and retake strategies. In general, the participants signaled a high engagement of the teaching group in making remote practical classes possible, overcoming the limitations and difficulties arising from the new format. Institutional restrictions to enable emergency remote teaching were indicated as a factor to be reviewed. And difficulties in simulating professional practice, which requires adequate physical structure and equipment, proved unavailable in the homes of teachers and students. It is considered that the implementation of remote teaching in practical classes was successful in many aspects, it enabled the on-the-job training of teachers and generated new alternatives to make such classes viable, in view of some restrictions that already persist in face-to-face teaching.
Keywords: Scientific and Technological Education; Educational Technologies; Emergency Remote Teaching; Pedagogical Model; Gastronomy